Vertical distribution and pollution assessment of TN, TP, and TOC in the sediment cores of cage farming areas in Dongshan Bay of southeast China - Zhen-Zhen, Cai; Jian, Zeng; Miao-Feng, Yang; Yong-Qing, Lin; Hui-Dong, Zheng; Dong-Lian, Luo; Shuang-Cheng, Jiang; Tuan-Yu, Guo; Sheng-Hua, Zheng (Frontiers in Environmental Science, 2023)
Cage farming is an important means of aquacultural production, while its potential environmental pollution needs to be further investigated. In this study, Dongshan Bay was taken as an example to investigate whether long-term cage farming in a semi-closed bay would cause environmental pollutions via vertical distribution assessment. The four sediment cores (YB1, YB2, B1, and B2) were collected from two cage farming areas.Total nitrogen (TN), total organic carbon (TOC), and total phosphorus (TP) were measured. The results showed a negative correlation between TN and TOC and the sediment depth at four sampling sites, and TP was also negatively correlated with the depth at three sites.